Kinetics and Mechanism of Oxidation of Some meta- and para-Substituted Phenoxyacetic Acids by N-Chloropiperazine-2,5-dione in Non-aqueous Medium - Palaniappan, An.; Srinivasan, S.; Senthilkumar, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of a number of meta- and para-substituted phenoxyacetic acids by N-chloropiperazine-2,5-dione (NCPD) have been studied in methanol medium. The reaction shows unit order dependence with respect to oxidant and the order with respect to substrate varies depending on the nature of the substituent present in the ring. The rate is showing an inverse order of dependence with respect to [TsOH]. The rate increases with decrease in the percentage of methanol. Increse in ionic strength has no effect on the reaction rate . From the kinetic data obtained the activation parameters have been computed and a suitable mechanism has been proposed in accordance with multiparameter correlation analysis.